高中性別平等教育師資培力課程架構及課程認證之初探 A Preliminary Study on Teacher Professional Development Courses and Certification of Gender Equity Education for High School Teachers - 呂明蓁 Meg Ming-Chen Lu; 蕭宇 Yu Hsiao; 吳星宏 Hsing-Hung Wu (Higher Education Foundation, 2022)
2010年公布的《性別平等教育白皮書》揭示教育主管機關應「定期辦理教育人員性別平等教育資格認證」並「鼓勵學校優先聘用具有相關認證資格之教師」，然校園中的性別平等教育依《性別平等教育法》之規定及國民教育階段學校施行現況皆以「融入」領域／學科／群科課程與教學為主。性別平等教育既非正式課程，無專屬授課時數，故無法進行師資專長資格認證。本研究係專案委託研究報告之部分成果，以建構符合培力性別平等教育師資性別平等意識及課程教學融入知能之專業課程架構為目的，使用教育部於2015年及2017年完成之兩份師資認證課程成果報告為基礎文本，分析其建議之師資認證課程架構，並使用問卷調查了解高中教師之需求，從而建立高中性別平等教育師資培力課程之架構。 The White Paper on Gender Equity Education released in 2010 reveals that competent education authorities should "conduct gender equity education certification of educators regularly" and "encourage schools to give priority to the recruitment of teachers with relevant certification." However, based on the provisions of Gender Equity Education Act, gender equity education implemented in schools in the national education stage focuses on "mergence" of gender equity and field/disciplinary/group courses and teaching. As to say, gender equity education is not only an informal course but also has no designated course hours, so teacher licensure for gender equity education cannot be carried out. This research is the first part of an ongoing project, which aims to construct a professional development course structure that conforms to gender equity awareness and empowers high school teachers with the knowledge and skill for integrating gender equity into teaching. This research uses the project reports from two former research projects on gender equity education training and certification for elementary and junior high school teacher as text materials. In addition to studying and analyzing the course structure and recommendations from former project reports, a questionnaire is also used to understand the needs of current high school teachers, so as to establish a set of gender equity education training courses for high school teachers.